Malignant Tumors Misdiagnosed as Liver Hemangiomas - Yıldırım, Murat Baki; Şahiner, İbrahim Tayfun; Poyanlı, Arzu; Acunaş, Bülent; Güllüoǧlu, Mine; İbiş, Cem; Tekant, Yaman; Özden, İlgin (Frontiers in Surgery, 2021)
Background and Aim: To derive lessons from the data of patients who were followed for various periods with the misdiagnosis of liver hemangioma and eventually found to have a malignancy. Material and methods: The records of 23 patients treated between 2003 and 2018 were analyzed retrospectively. Results: Twelve patients were men and 11 were women; median (range) age was 55 (35-80). The principal diagnostic modality for the initial diagnosis was ultrasonography (n:8), magnetic resonance imaging (MRI) (n: 13) and computed tomography (CT) (n: 2). At our institution, MRI was performed in 16 patients; the diagnosis was made with the available MRI and CT studies in 5 and 2 patients respectively. In other words, the ultrasonography interpretations were not confirmed on MRI; in others, the MRI or CT examinations were of low quality or they had not been interpreted properly. Fifteen patients underwent surgery; the other patients received chemotherapy (n:6) or chemoembolization (n:2). The misdiagnosis caused a median (range) 10 (0-96) months delay in treatment. The final diagnoses were hepatocellular carcinoma in 12 patients, cholangiocarcinoma in 4 patients, metastatic mesenchymal tumor, metastasis of colon cancer, metastatic neuroendocrine carcinoma, sarcomatoid hepatocellular carcinoma, angiosarcoma, thoracic wall tumor and metastatic tumor of unknown primary in one patient each. Conclusions: High-quality MRI with proper interpretation and judicious follow up are vital for the accurate differential diagnosis of liver lesions.